An Economic Analysis of Municipal Solid Waste Management of Toyohashi City, Japan: Evidences from Environmental Kuznets Curve - Yuzuru Miyata; Hiroyuki Shibusawa; Nahid Hossain (European Regional Science Association (ERSA), 2013)
The study of Toyohashi cityfs economic growth and resultant growth in municipal solid waste management were empirically examined by the relation between city economic growth, city expenditure for solid waste management and municipal solid waste. The growth in the economy and the population has increased discharge of municipal solid waste in Toyohashi city. The economic size of the city is identified as a strong explanatory variable. Various kinds of municipal solid waste were generated with the city growth. Our study found that during the period of 1980 to 2005, Toyohashi city grew fast and, disposal municipal solid waste of the city was increased as a by-product of economic activities. Such increase in solid waste disposal put in more on demand for policy and technological interventions. As a result, the city expenditures on waste management increased during the same period. The city opened its high-tech waste treatment facility in 1984. The facility provides waste to heat and power generation technology (Toyohashi city, 2011). Later on, the national concept of the sound-material based society supports the city to initiate efficient and effective municipal waste management strategy from 2001 onward (Tachibana, et al., 2008). The positive coefficient of economic level for generation of municipal solid waste was positive. The result denotes that economic growth put upward pressure to the municipal solid waste generation. The negative coefficient of (economic level)2 indicates governmental initiative to manage the municipal solid waste generation in terms of regulations and/or technology was successful in case of Toyohashi city. The coefficient of per capita city expenditures for generation of municipal solid waste was positive and the expenditures on management of the municipal solid waste grew steadily. The result implies that the higher the waste generated, the more the city needs to spend more for waste management. The negative coefficient of per capita (city expenditures)2 indicates technological and regulatory intervention was appropriate to manage the waste generated by the city. The results provide theoretical and practical significance and proposition. The growth of Toyohashi city was positively correlated to produce higher municipal solid waste while better regulatory intervention and technological improvement could end up well management of the waste generated.
Keywords: Q50; Q56; 330; Environmental Kuzunets Curve; Waste; Toyohashi; Japan